(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research is entitled “The Role of Pasundan People’s Party in Pasundan State from 1947-1950”. The main problem is to find out “How was the role of the Pasundan people’s party in the Pasundan state from 1947-1950?”. The method used in this research is the historical method. The author concluded that the formation of Partai Rakyat Pasundan was motivated by Suria Kartalegawa’s intention to lead West Java and supported by the Dutch who also wanted to form a Federal State in Indonesia. Suria Kartalegawa as a founding figure played an important role in the formation of the Pasundan People’s Party which later declared the Pasundan State. The activities of the Pasundan People’s Party in the government of the Pasundan State which divided into two, the first one is the Pasundan State declared by Suria Kartalegawa and the second one is the Pasundan State as a result of the West Java Conference. Suria Kartalegawa’s version of the Pasundan State did not last long due to the lack of support from several elements of society, both from figures or the West Java community itself, and was considered a counter revolutionary movement. Then the Pasundan version of the West Java Conference led by Wiranatakusumah V produced three West Java conferences, in this period Suria Kartalegawa and his Pasundan People’s Party were more active in the Pasundan State Parliament withstand more in the opposition side. The Pasundan People’s Party fainted and disbanded itself following the disbandment of the Pasudan State in 1950 and the arrest of Suria Kartalegawa, and then West Java again became part of the Republic of Indonesia.